FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN INFORMASI AKUNTANSI PADA USAHA KECIL DAN MEN - Linear Diah Sitoresmi; Fuad Fuad (Diponegoro Journal of Accounting, 2013)
Incapability in using accounting information is one of the factors that led to the failure of SMEs in developing their business. The purpose of this research was to determine the effect of owner’s education, business size, firm age and training on accounting on the use of accounting information by the environmental uncertainty as a moderating variable on small and medium enterprises in Semarang. The population in this research are members of KUB Sido Rukun Semarang. The sampling method using Simple Random Sampling amounted to 51 owner or manager of the company. The data was collected by distributing questionnaires to the owners/managers of small and medium enterprises. Techniques of data analysis using multiple linear regression analysis and residual test. Results of this research indicate that owner’s education, business size, firm age and training on accounting significantly effect on use of accounting information. Environmental uncertainty doesn’t moderate the effect of owner’s education, business size, firm age and training on accounting on the use of accounting information.